2009
DOI: 10.4103/0974-2727.59702
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Latex Agglutination in Cryptococcal Meningitis

Abstract: Background:Cryptococcus neoformans is the most common fungal pathogen to infect the central nervous system, and an effective diagnostic method is therefore necessary for the early diagnosis of cryptococcal meningitis.Aim:The efficacy of India ink preparation, cerebrospinal fluid (CSF) culture and CSF cryptococcal antigen detection by the latex agglutination test for diagnosis of cryptococcal meningitis are compared to determine the most efficient test.Materials and Methods:Two hundred CSF samples from human im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 13 publications
3
13
0
Order By: Relevance
“…Mycological diagnosis is a reference method because the sensitivity and specificity are close to 100% [24,33]. Culture is considered to be the ''gold standard'' method of diagnosis for C. neofromans, but it takes at least 3 days to a maximum time of a month for growth [34]; knowing that the CSF analysis is an emergency in a clinical biology laboratory, it is important to have more rapid and efficient diagnosis approaches for diagnosing cryptococcal meningitis. The India ink test in this study showed sensitivity and specificity values higher than what obtained by Soumaré et al [36].…”
Section: Cryptococcosismentioning
confidence: 99%
“…Mycological diagnosis is a reference method because the sensitivity and specificity are close to 100% [24,33]. Culture is considered to be the ''gold standard'' method of diagnosis for C. neofromans, but it takes at least 3 days to a maximum time of a month for growth [34]; knowing that the CSF analysis is an emergency in a clinical biology laboratory, it is important to have more rapid and efficient diagnosis approaches for diagnosing cryptococcal meningitis. The India ink test in this study showed sensitivity and specificity values higher than what obtained by Soumaré et al [36].…”
Section: Cryptococcosismentioning
confidence: 99%
“…However, this delay from suspicion to diagnosis is often unacceptable in the case of such a serious infection, and therefore, alternative screening tests that allow for timely treatment initiation are often performed as adjuncts to culture. Perhaps the oldest method that is still used in clinical laboratories involves staining of the CSF with India ink, which allows visualization of the cryptococcal cells under the microscope, as round, encapsulated yeast organisms, in more than 75% of patients (94). The most accurate screening method, however, is the cryptococcal antigen test.…”
Section: Other Fungal Infectionsmentioning
confidence: 99%
“…In 14 patients India ink test was observed to be negative while their culture was positive. This emphasises on the limited sensitivity of India ink as a screening test, which depends upon both fungal burden and capsule production and even small discrepancies often lead to false negative results [9].…”
Section: Methodsmentioning
confidence: 99%